Penerapan Model Number Head Together untuk Meningkatkan Hasil Belajar Tematik Terpadu Siswa di Kelas IV SDN 20 Sitiung, Kab. Dharmasraya - Muliani Muliani (Universitas Negeri Padang, 2021)
The purpose of this study is to describe the use of the Number Head Together model to improve integrated thematic learning outcomes in the fourth grade of SDN 20 Sitiung Kab. Dharmasraya. This type of research is Classroom Action Research (CAR) using a qualitative and quantitative approach. This research was conducted in two cycles. Each cycle consists of planning, implementing, observing, and reflecting. The subjects in this study were teachers as observers, researchers as practitioners, and 28 students of grade IV SD N 20 Sitiung.The conclusions of this study are: 1) The assessment of the percentage of RPP has increased from the previous 82.13% in the first cycle to 89.28% in the second cycle. 2) The teacher aspect has increased from 84.37% to 90.62%. 3) The student aspect has increased from 84.37% to 90.62%. 4) Student learning outcomes have increased from the first cycle to get the percentage of completeness 53.57% increased to 85.71% in the second cycle.